2019
DOI: 10.1007/s10290-019-00367-w
|View full text |Cite
|
Sign up to set email alerts
|

Does the GATT/WTO promote trade? After all, Rose was right

Abstract: This paper re-examines the effect of the GATT/WTO on trade using recent econometric developments that allow us estimating structural gravity equations with the Poisson pseudo-maximum likelihood (PPML) estimator on a large dataset that requires computing high-dimensional fixed effects. By doing so, we overcome computational limitations that are present in previous studies. In line with Rose's (Am Econ Rev 94: [98][99][100][101][102][103][104][105][106][107][108][109][110][111][112][113][114] 2004) seminal work,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 58 publications
0
19
0
Order By: Relevance
“…By controlling these aspects, the author suggests that the WTO did not promote trade. Esteve‐Pérez et al (2020) reached the same conclusion using the PPML estimator with three types of fixed effects, simultaneously accounting for unobserved bilateral heterogeneity and endogeneity (with country‐pair fixed effects) and multilateral resistance terms (with exporter‐time and importer‐time fixed effects) in a large dataset with more than 200 countries over the period 1948–2013.…”
Section: Wto Asymmetries and Effects On Tradementioning
confidence: 65%
See 2 more Smart Citations
“…By controlling these aspects, the author suggests that the WTO did not promote trade. Esteve‐Pérez et al (2020) reached the same conclusion using the PPML estimator with three types of fixed effects, simultaneously accounting for unobserved bilateral heterogeneity and endogeneity (with country‐pair fixed effects) and multilateral resistance terms (with exporter‐time and importer‐time fixed effects) in a large dataset with more than 200 countries over the period 1948–2013.…”
Section: Wto Asymmetries and Effects On Tradementioning
confidence: 65%
“…Dutt et al (2013) included zeros when adopting the two‐stage estimator proposed by Helpman et al (2008), (henceforth HMR), but they did not take into account existing WTO asymmetries. Esteve‐Pérez et al (2020) used the PPML estimator and three types of fixed effects, but only on aggregate trade flows. Therefore, none of the studies cited used the PPML estimator to analyse the effects of the WTO on disaggregated trade flows, to the best of our knowledge.…”
Section: Wto Asymmetries and Effects On Tradementioning
confidence: 99%
See 1 more Smart Citation
“…An alternative and more robust approach to the ad‐hoc shifted log specification is the Poisson pseudo maximum likelihood (PPML) method suggested by Silva and Tenreyro (2006, 2011). This approach has become a standard tool in the trade literature when a data set has many zero values in the dependent variable (Esteve‐Pérez, 2020). Silva and Tenreyro (2006, 2011) demonstrated that PPML models perform better than OLS in the presence of heteroscedasticity and many zero observations.…”
Section: Empirical Analysismentioning
confidence: 99%
“…Most studies have shown that the introduction of the euro had a positive and significant effect on trade among eurozone members (Cieślik et al 2012;Camarero et al 2014;Glick and Rose 2016;Kunroo et al 2016;Larch et al 2018;Esteve-Pérez et al 2020). Meanwhile, Santana-Gallego et al (2016) assess the positive impact of the euro on tourism flows.…”
mentioning
confidence: 99%